Weaving a library Web : a guide to developing children's websites - Blowers, Helene (American Library Association, 2004)
Eager to feed their curiosity with interactive information, children are becoming more responsive to technology, and many now use a mouse more effectively than a crayon. By embracing the possibilities of the Internet when programming for children, libraries can empower the young with great information while supplementing traditional children's services.